A notoriedade da saga Harry Potter. - Torres, José Reinaldo da Silva (Universidade Federal do Tocantins, 2024)
This study aimed at understanding how the popularity of the Harry Potter book saga by British author J. K. Rowling was formed and developed, since the beginning of its first publication. The present work presents its methodology in a bibliographical research around the studies of TODOROV (1939) about the fantastic in literature; the readaptation of the Storytelling method “The Hero's Journey” by VOGLER (1992), used in the research in a brief analysis in the book “Harry Potter and the Sorcerer's Stone” (2000); as well as present literary criticisms about the reception of books for the genre market. From all the information obtained, a reflection was carried out on the differential present in Rowling's narrative and, on how the books managed to attract attention, converting a legion of fans and readers around the world, remaining in the spotlight for different generations after two decades since its publication.